Electro-taichi stimulator - Tan, Zheng Chuan. (2013)
Taichi is a widely practiced Chinese Martial Arts based on slow sequential movements. It is well known for its health benefits, illness prevention, stress reduction and well being of individuals. Taichi has become a popular activity in many Asian countries. Discovering the numerous benefits of Tiachi, we are motivated to design an Electro-Taichi stimulator, which will bring similar benefits of Taichi to immobile individuals. A concurrent project translates the Taichi 24 forms into a stimulation algorithm. My project involves the design and implementation of the hardware and software needed to implement the stimulation algorithm. This project requires the proper selection of appropriate hardware and software and chips to provide supporting functions of the stimulator. After building the hardware, I have written the program to implement the Taichi 24 form algorithm. Many hardware and software challenges were encountered in this project. Most of the problems encountered were solved. The final product is housed in a rectangular plastic container for portability. We have also proposed further enhancement for this project in our conclusion.